Phosphoglycerate kinase 1 as a potential prognostic biomarker in papillary thyroid carcinoma - Shi, Xiao-Qing; Liu, Xiao-Tong; Liu, Xiao-Hui; Geng, Hui-Wen; Zhang, Zhuo; Wang, Wei-Yi; Chen, Xing; Zhao, Xian; Jue, Bo-Lin; Qin, Bo; Liu, Pei-Pei (Frontiers in Pharmacology, 2025)
BackgroudPapillary thyroid carcinoma (PTC) represents a malignant epithelial tumor characterized with a preference for younger individuals. Despite its generally favorable prognosis, PTC still poses considerable challenges, particularly in regards to the propensity for distant metastasis. As a key enzyme in the glycolytic pathway, phosphoglycerate kinase 1 (PGK1) has been linked to the progression of various cancer types. However, its role in PTC remains to be elucidated. This study aimed to investigate the association between PGK1 expression in thyroid cancer tissues and clinicopathological features, postoperative recurrence, and prognosis to provide clinical assessment and intervention reference.MethodsWe investigated the correlation between PGK1 expression and the clinicopathological characteristics, recurrence, and prognosis in 97 PTC patients who underwent surgical treatments between 1 January 2020, and 31 December 2020 in Zhengzhou University First Affiliated Hospital. Besides, we also analysed the correlation of PGK1 expression with the 10-year survival rate of patients with thyroid carcinoma (THCA) in UALCAN database.ResultsPGK1 expression was higher in cancerous tissues than that in adjacent non-cancerous tissues. Further analysis of PGK1 expression across clinicopathological characteristics revealed that patients with poorly differentiated tumors, TNM stages III–IV, lymph node metastasis, and tumor diameter ≥1.0 cm exhibited higher PGK1 expression levels in cancerous tissues. A subsequent 3-year postoperative follow-up was conducted to evaluate the correlation between PGK1 expression and recurrence. During this period, 31.96% of patients experienced recurrence, with higher PGK1 expression correlating with increased recurrence rates. Moreover, patients with higher PGK1 expression in cancerous tissue exhibited a significantly lower survival rate of 79.20% compared to the PGK1-low/medium group. Lastly, age, lymph node metastasis, differentiation degree, TNM stage, and tumor diameter were identified as risk factors for poor prognosis in patients with PTC analyzed by Cox regression.ConclusionOur study demonstrated that PGK1 expression may serve as a potential prognostic biomarker of PTC.